2010
DOI: 10.1080/08927010903277749
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the biofouling and cleaning efficiency of nanofiltration membranes

Abstract: The nanofiltration (NF) drinking water production unit of the Mery-sur-Oise plant (Val d'Oise, France) consists of eight identical filtration trains composed of three stages positioned in steps for a production capacity of 140,000 m(3) day(-1). To gain a better understanding of the irreversible fouling of the NF membranes, spiral wound modules in operation for 8 years from each of the three stages of the plant were autopsied before and after chemical cleaning and analysis by Attenuated Total Reflection Fourier… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 20 publications
0
15
0
Order By: Relevance
“…This can be achieved by managing feedwater, operational conditions (flux, hydrodynamics) [13], cleaning strategies [131] and membrane selection. However, the costs associated with membrane cleaning and the costs associated with the increased energy expenditure in NF/RO operations under moderate biofouling necessitate further basic research into fundamental mechanisms governing biofilm development in NF/RO modules [112]. As part of this strategy is the need for a better understanding of bacterialmembrane interactions, an area of research that has not received priority but is nevertheless critical in order to fully understand several important aspects of NF/RO biofouling.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This can be achieved by managing feedwater, operational conditions (flux, hydrodynamics) [13], cleaning strategies [131] and membrane selection. However, the costs associated with membrane cleaning and the costs associated with the increased energy expenditure in NF/RO operations under moderate biofouling necessitate further basic research into fundamental mechanisms governing biofilm development in NF/RO modules [112]. As part of this strategy is the need for a better understanding of bacterialmembrane interactions, an area of research that has not received priority but is nevertheless critical in order to fully understand several important aspects of NF/RO biofouling.…”
Section: Discussionmentioning
confidence: 99%
“…However, these studies were carried out at very low pressure conditions of less than 2.5 bar, when realistically the pressures used for NF and RO membranes in water treatment can go up to at least 17 bar [112]. Another study showed that under the same flux conditions the biofilm formed on the surface of three different RO membranes had similar characteristics.…”
Section: Hydrodynamics and Mass Transportmentioning
confidence: 99%
See 1 more Smart Citation
“…NF is principally used for the removal of hardness, trace contaminants, such as pesticides and organic matter (Cyna et al (2002)), while RO is used for desalination (Greenlee et al (2009)). NF and RO performance are however adversely affected by biofilm formation resulting in permeate flux and quality decline (Flemming (1997), Houari et al (2009), Ivnitsky et al (2007), Khan et al (2013), Vrouwenvelder et al (1998), Vrouwenvelder et al (2008)), generally caused by the initial adhesion and subsequent colonization of bacterial cells on the surface of the membrane, amalgamating in a biomass consisting of, and not limited to, polysaccharides, proteins, and extracellular DNA (Pamp et al (2007)). …”
Section: Introductionmentioning
confidence: 99%
“…Different types of NF fouling can be defined on the basis of fouling material: inorganic fouling due to deposition on membrane surface of inorganic scales; organic fouling due to humic acids, proteins and carbohydrates (natural organic material, NOM); biofouling due to biofilm formation at the membrane surface. Flux decline associated with NOM fouling and with biofouling can be partially restored by chemical cleaning (Al-Amoudi et al 2005, Houari et al 2010, Roudman et al 2000. Biofouling is distinct from NOM fouling caused by contaminated organic matter derived from biological systems (Flemming et al, 1997).…”
Section: Introductionmentioning
confidence: 99%